Rotational changes and associated risk factors following intramedullary nail fixation for intertrochanteric femoral fractures in elderly patients - Han, Chao; Li, Xiaodan; Han, Zhe; Dong, Qiang (Frontiers in Surgery, 2025)
ObjectiveTo quantify rotational displacement following intramedullary nail fixation for intertrochanteric femoral fractures using three-dimensional (3D) CT imaging, analyze associated risk factors, and evaluate its clinical significance.MethodsA total of 210 patients who underwent intramedullary nail fixation for intertrochanteric femoral fractures between 2020 and 2022 were included. All patients received postoperative 3D CT scans and were followed for at least 1 year. The range of postoperative femoral anteversion on the affected side was measured, and its correlation with risk factors was analyzed.ResultsAmong the 210 participants: six patients exhibited anteversion changes exceeding 15°; seven patients had anteversion changes between 10° and 15°; forty-three patients showed reduced anteversion (indicating increased external rotation of the affected limb), ranging from −1° to −14°, with a mean of −2.58°; in 103 patients, anteversion increased postoperatively, ranging from 1° to 22°, with a mean of 3.90°; sixty-four patients achieved restoration of normal anteversion. Single-nail fixation, poor reduction quality, medial cortical defects, T-score ≤ −2.5, Singh's index (Ⅰ–Ⅲ), lateral wall thickness, and insufficient tip-apex distance (TAD) were identified as the primary factors contributing to rotational displacement exceeding 3°. At the 1-year follow-up, patients with smaller rotational displacement demonstrated better functional recovery. The multivariate logistic regression analysis demonstrated that several factors showed significant correlations with rotational displacement of fracture fragments after intramedullary nail fixation, including the severity of medial cortical defects, presence of medial cortical disruption, T-scores ≤ −2.5, low-grade Singh's index classifications (I–III), diminished lateral wall thickness, inadequate TAD, Visual Analog Scale (VAS), and the Harris Hip Score (HHS).ConclusionBone rotation and displacement are frequently observed following intramedullary nail fixation for intertrochanteric fractures. Numerous risk factors are closely associated with these complications. Therefore, meticulous attention to surgical technique is essential to minimize complications and optimize outcomes.